2006
DOI: 10.1007/s10162-006-0035-x
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of SLC19A2, the High Affinity Thiamine Transporter, Causes Selective Inner Hair Cell Loss and an Auditory Neuropathy Phenotype

Abstract: Mutations in the gene coding for the high-affinity thiamine transporter Slc19a2 underlie the clinical syndrome known as thiamine-responsive megaloblastic anemia (TRMA) characterized by anemia, diabetes, and sensorineural hearing loss. To create a mouse model of this disease, a mutant line was created with targeted disruption of the gene. Cochlear function is normal in these mutants when maintained on a high-thiamine diet. When challenged with a low-thiamine diet, Slc19a2-null mice showed 40-60 dB threshold ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 15 publications
3
53
0
3
Order By: Relevance
“…Therefore, we consider it likely that thiamine deficiency impairs IHC function before causing loss of IHCs. In conclusion, thiamine deficiency can cause audi tory neuropathy, but the disease mechanisms in hearing impairment associated with thiamine deficiency await further analysis in appropriate animal models 110 .…”
Section: Ihc Loss Underlies Thiamin-deficiency-related Auditory Neuromentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, we consider it likely that thiamine deficiency impairs IHC function before causing loss of IHCs. In conclusion, thiamine deficiency can cause audi tory neuropathy, but the disease mechanisms in hearing impairment associated with thiamine deficiency await further analysis in appropriate animal models 110 .…”
Section: Ihc Loss Underlies Thiamin-deficiency-related Auditory Neuromentioning
confidence: 97%
“…Most of these infants showed auditory neuropathy, which resolved with supplementary thia mine in five of eight children; two of these infants lacked otoacoustic emissions, suggesting OHC dysfunction 108 . The importance of thiamine for cochlear function was convincingly demonstrated in studies of mice that lacked highaffinity thiamine transporter, which is encoded by Slc19a2 (REFS 109,110). In one of these studies, a massive and rapid loss of IHCs was observed upon dietary thi amine restriction 110 .…”
Section: Ihc Loss Underlies Thiamin-deficiency-related Auditory Neuromentioning
confidence: 97%
See 1 more Smart Citation
“…SLC19A2 nakavt fare modellerinde tiamin düzeyleri düştü-ğünde, insülin sekresyonunda kusur ve kohlear tüysü hücrelerde seçici kayıp olduğu görülmüştür. 3 Megaloblastik aneminin patogenezi tam olarak açıklanamamaktadır. Timin transportundaki bozukluk sonucu hücre içi timin düzeyinin düşmesi ve kusurlu RNA riboz sentezinin megaloblastik değişikliklere yol açtığı düşünülmektedir.…”
Section: Discussionunclassified
“…Ancak, hayvan modellerinde kohleanın histopatolojik incelemesinde içteki tüysü hücrelerde dejenerasyon saptanmıştır. 3 Olgumuza yapılan işitsel beyin yanıtı (ABR-BERA) testinde işitme kaybının olduğu saptandı. Öyküsünden, doğumda yapılan işitme taramasının normal sonuçlandığı öğ-renildi.…”
Section: Discussionunclassified